Gender and Climate Smart Agriculture in East Africa: Trends and Impacts - Omolo, Nancy (2024)
"Women and men have different roles, responsibilities, and decision-making authority on farms in East Africa. Women are almost exclusively responsible for childcare and household maintenance and thus need to undertake more tasks in a working day. At the same time women often have very different off-farm income-generation opportunities to men, are usually paid less as casual labourers than men, and in general their work is less secure. Women and men in the region are experiencing climate change differently, given gender based inequalities in access to and control of productive and financial resources that inhibit agricultural productivity and reduce food security. Women in rural areas are more vulnerable to climate change and variability as a result of their natural resource- and environment-based activities, including agriculture."